Copper-Catalyzed Amidation of Arylboronic Acids with Nitriles - Huang, He; Jiang, Zhong-Tao; Wu, Yang; Gan, Cheng-Yan; Li, Jin-Mei; Xiang, Shi-Kai; Feng, Chun; Wang, Bi-Qin; Yang, Wei-Te (Synlett, 2016)
A copper-catalyzed amidation of arylboronic acids with nitriles has been developed. This reaction provides an efficient and complementary methodology for the synthesis of various N-arylamides with a broad substrate scope.
Keywords: amides; nitriles; amination; copper; catalysis